Differential proteomic analysis of actinic keratosis, Bowen's disease and cutaneous squamous cell carcinoma by label-free LC–MS/MS. Issue 1 (July 2018) - Azimi, Ali; Kaufman, Kimberley L.; Ali, Marina; Arthur, Jonathan; Kossard, Steven; Fernandez-Penas, Pablo
Highlights: Actinic keratosis and Bowen's disease are precursors of cutaneous squamous cell carcinoma. Cell proliferation, angiogenesis, protein metabolism, and inflammatory reactions are activated in cutaneous squamous cell carcinoma compared to Bowen's disease and actinic keratosis. Cell death and DNA damage are inhibited in Bowen's disease compared to actinic keratosis and cutaneous squamous cell carcinoma. A handful of differentially abundant proteins are identified between cutaneous squamous cell carcinoma subtypes that will support a molecular classification of these lesions and will improve our understanding of disease progression. Abstract: Background: The boundaries between actinic keratosis (AK), Bowen's disease (BD), and cutaneous squamous cell carcinoma (cSCC) are sometimes not clear. Large-scale proteomic profiling studies of these lesions are also non-existent. Objective: To evaluate proteomic changes between normal epidermis, AK, BD and cSCC that could support a molecular classification and improve our understanding of disease progression. Methods: Microdissected formalin-fixed paraffin embedded samples of normal epidermis (n = 4, pooled), AK (n = 10), BD (n = 10) and cSCC (n = 10) were analyzed by mass spectrometry. Following normalization and multiple testing adjustments, differential abundance analysis was performed using Linear Models for Microarray data. Proteins were filtered for significance (adjusted p-value ≤ 0.05) and fold change of at least ±1.5. Comparative bioinformatics analysis was performed using Ingenuity Pathway Analysis (IPA) software. Proteomic findings were subsequently substantiated using immunohistochemistry. Results: 2073 unique proteins were identified. cSCC had the highest number of differentially abundant proteins (63 proteins) followed by BD (58 proteins) and AK (46 proteins). Six proteins (APOA1, ALB, SERPINA1, HLA-B, HP and TXNDC5) were differentially abundant in cSCC compared to AK. Immunohistochemical analysis corroborated changes in MIF, RPL37A and TXNDC5. IPA analysis predicted that cell proliferation, angiogenesis and inflammatory reactions were significantly activated in cSCC compared to BD and AK. Cell death and DNA damage were predicted to be inhibited in BD. Conclusion: Our study supports the concept that AK and BD are precursors of cSCC. The identification of proteome changes indicates disruption of repair, pro-apoptotic, and tumor promoting pathways. Our findings will help select targets for classification and treatment.